Gender differences in the associations between knee pain and urinary incontinence in older adults: Cross‐sectional analysis from the Malaysian Elders Longitudinal Research Study (MELoR). Issue 3 (2nd February 2023) - Mat, Sumaiyah; Jaafar, Mohamad Hasif; Razack, Azad H. A.; Lim, Jasmine; Ong, Teng Aik; Khong, Su‐Yen; Kamaruzzaman, Shahrul Bahyah; Chin, Ai‐Vyrn; Abbas, Azlina Amir; Chan, Chee Ken; Hairi, Noran Naqiah; Othman, Sajaratulnisah; et al.
Abstract: Introduction: The common assumption that urinary incontinence occurs in osteoarthritis (OA) due to poor mobility is supported by limited evidence. The influence of gender in such associations is also yet to be elucidated. Objective: This study, therefore, identified any potential associations between knee OA symptoms and urinary incontinence and further explore sex differences in the associations. Design: Cross‐sectional study. Setting: University Hospital. Participants: This was a cross‐sectional study from a longitudinal research study comprising 1221 community‐dwelling older persons (57% women), mean age (SD) 68.95 (7.49) years. Main Outcome Measure(s): Presence of urinary incontinence: mixed, stress and urge symptoms. Physical performance and C‐reactive protein levels were also assessed. Results: Two hundred and seventy‐seven (22.83%) individuals reported the presence of urinary incontinence: mixed (41.5%), stress (30%), and urge (28.5%) symptoms. In an unadjusted analysis, stratified by gender, the association between knee pain and urinary incontinence was only present in women with mixed symptoms. After further adjustment of demographics differences and body mass index, the association between knee pain with any urinary incontinence and mixed symptoms remained significant with the odds ratios (95% confidence interval): 1.48 (1.02–2.15) and 1.73 (1.06–2.83), respectively. This relationship was attenuated after further adjustment for waist circumference and impaired lower limb mobility. Conclusion: Our study refutes previous assumptions that urinary incontinence in individuals with OA is attributed to impaired mobility alone, but introduces the role of abdominal obesity in this relationship, particularly in women. Future studies should assess the temporal relationship between body fat distribution and OA with urinary incontinence.